Phagocytosis of staphylococci by human polymorphonuclear leukocytes is enhanced in the presence of endothelial cells. - Vandenbroucke-Grauls, C M (1985)
The role of various surfaces in the phagocytosis of Staphylococcus aureus by human polymorphonuclear leukocytes (PMN) was studied. Uptake of both opsonized and unopsonized staphylococci on the surface of a monolayer of human venous endothelial cells was compared with uptake on an inert plastic surface, with an assay that uses radiolabeled bacteria. Uptake of unopsonized S. aureus was threefold higher on the endothelial cell surface than on the plastic surface and was followed by efficient killing of the phagocytosed staphylococci. Uptake of unopsonized S. aureus on endothelial cells was not inhibited by treatment of the PMN with pronase or 2-deoxy-D-glucose and was only partially inhibited by cytochalasin B treatment of the PMN. The supporting effect of endothelial cells on the phagocytosis of unopsonized S. aureus was not due to opsonization of the bacteria by immunoglobulin or complement from the endothelial cell surface, nor to coating with fibronectin.